DISKUSI MENGENAI PERENCANAAN STRATEGIS DALAM PERGURUAN TINGGI DAN INOVASI DALAM PENDIDIKAN - Setiadi Umar (Bina Ekonomi, 2007)
Every company needs strategic planning to deal with its external environment and to achieve its vision and long-term and short-term goals. In general a typical strategic plan starts with a lengthy description of current industry conditions and the competitive situation to be followed by the discussion of how to increase market shares, capture new segments, or cut costs, followed by an outline of numerous goals and initiatives. The process usually culminates in the preparation of a large document culled from a mishmash of data provided by people from various parts of the organization who often have conflicting agendas and poor communication. In this process, managers spend the majority of strategic thinking time filling in boxes and running numbers instead of thinking outside the box and developing a clear picture of how to break away from competition. It is no wonder that only few strategic plans lead to the creation of blue oceans or are translated into action. Few employees deep down in the company even know what the strategy is. And a closer look reveals that most plans do not contain a strategy at all but rather a smorgasbord of tactics that individually makes sense but collectively does not add up to a unified, clear direction that sets a company apart, let alone makes the competition irrelevant. The strategic planning process should not be based on preparing a document, but on drawing a strategy canvas that focuses on the big picture and not the numbers. This paper starts with a discussion of competitive environment in higher education institutions, such as colleges and universities, where many institutions are competing on the same key success factor and the same competitive rules of competing and many offer the same offering. These situations make the higher education institutions face intense competition, mounting price pressure, and flat demand. Therefore this paper will discuss ideas and steps that could be taken to open the paths to creating blue oceans.